Effect of oral nutrition supplement on growth in preschool children – a systems physiology-based in silico analysis - V, Hari Nishanthi; Chheda, Ekta; Gurumaani, Siranjeevi; Gangwar, Vani; Saxena, Abha; Lomore, Karan; Marathe, Madhavi; Rahul, Preethi; Kareenhalli, Venkatesh (Indian Journal of Child Health, 2022)
Introduction: Optimum nutrition is the cornerstone of child growth and development. Childhood is a period of rapid growth and development. Children of preschool age have higher nutritional needs and are often at risk of nutrient deficiencies. Objective: The present study was designed to evaluate the effect of an oral nutritional supplement (ONS) on growth parameters in a representative population. Methods: We used the systems-biology-based mathematical model for child growth to analyze the effect of ONS on growth in a representative in silico population of preschool children. The analysis included changes in average growth velocities of weight, height, muscle mass, fat mass, fat-free mass, and bone mass. We used meta-data analysis for evaluating the absorption of micronutrients present in the ONS that affects growth in preschool children. Results: The results of the analysis showed one serving of ONS in milk/day improved the weight gain velocity by 1.7 times in preschool children. The linear growth was 1.04 times higher than the control. The absorption of micronutrients such as iron, vitamin K, calcium, and magnesium was higher in the ONS group. Conclusions: This study indicates that the ONS containing macro and micronutrients, docosahexaenoic acid (DHA), and prebiotics can potentiate growth and development in preschool children. It provides micronutrients that can be readily absorbed which are essential for other vital functions in the body.